Analyzing single system design data - Nugent, William R. (New York ; Oxford : Oxford University Press, 2009)
Covering the visual, graphical, and statistical analysis of data from single-case studies, this book offers a much more comprehensive coverage of the range of data analysis methods than is contained in any other books on the topic for social workers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Statistical methods